2018
DOI: 10.5194/acp-18-7607-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the chemical fingerprint of biomass burning organic aerosol during aging

Abstract: Abstract. A thermal desorption aerosol gas chromatograph coupled to a high resolution -time of flight -aerosol mass spectrometer (TAG-AMS) was connected to an atmospheric chamber for the molecular characterization of the evolution of organic aerosol (OA) emitted by woodstove appliances for residential heating. Two log woodstoves (old and modern) and one pellet stove were operated under typical conditions. Emissions were aged during a time equivalent to 5 h of atmospheric aging. The five to seven samples were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 80 publications
(94 reference statements)
11
76
1
Order By: Relevance
“…These compounds are consistent with products from lignin pyrolysis ( Fig. S4, Bertrand et al, 2017Bertrand et al, , 2018 and contributed significantly to the CHO signal recorded for primary wood-burning emissions but less for aged emissions (57 %,49 %,44 % of CHO aromatic;5 %,3 %,3 % of condensed aromatic;and 38 %,48 %,53 % of non-aromatic for fresh, 10 h, and 30 h atmospherically aged emissions, respectively). The ambient wood-burning pollution showed a similar distribution of the CHO signal as aged laboratory wood-burning emissions (Magadino -46 % aromatic, 6 % condensed aromatic, 48 % non-aromatic; San Vittore -44 % aromatic, 4 % condensed aromatic, 52 % non-aromatic), and the detailed chemical composition was similar to the fresh laboratory woodburning emissions (Fig.…”
Section: Chemical Compositionsupporting
confidence: 81%
See 1 more Smart Citation
“…These compounds are consistent with products from lignin pyrolysis ( Fig. S4, Bertrand et al, 2017Bertrand et al, , 2018 and contributed significantly to the CHO signal recorded for primary wood-burning emissions but less for aged emissions (57 %,49 %,44 % of CHO aromatic;5 %,3 %,3 % of condensed aromatic;and 38 %,48 %,53 % of non-aromatic for fresh, 10 h, and 30 h atmospherically aged emissions, respectively). The ambient wood-burning pollution showed a similar distribution of the CHO signal as aged laboratory wood-burning emissions (Magadino -46 % aromatic, 6 % condensed aromatic, 48 % non-aromatic; San Vittore -44 % aromatic, 4 % condensed aromatic, 52 % non-aromatic), and the detailed chemical composition was similar to the fresh laboratory woodburning emissions (Fig.…”
Section: Chemical Compositionsupporting
confidence: 81%
“…The chemical analyses were complemented with other filterbased analyses. Organic and elemental carbon (OC, EC) concentrations were determined for Zurich, Magadino, San Vittore, and Hyytiälä by a thermo-optical transmission (TOT) method with a Sunset OC/EC analyser (Birch and Cary, 1996), following the EUSAAR-2 thermal-optical transmission protocol (Cavalli et al, 2010). Water-soluble inorganic ions (K + , Na + , Mg 2+ , Ca 2+ , NH + 4 ; and SO 2− 4 , NO − 3 , Cl − ) were measured by ion chromatography for Zurich, Magadino, and San Vittore (Piazzalunga et al, 2013;Jaffrezo et al, 1998).…”
Section: Other Chemical Analysesmentioning
confidence: 99%
“…Rapid oxidation was also observed in studies of biomass burning organic aerosol in Africa (Capes et al, 2008;Vakkari et al, 2014), over the Mediterranean Sea (Bougiatioti et al, 2014), and Hyytiälä, Finland Vogel et al, 2013). Other studies focused on the oxidation of molecular tracers such as levoglucosan have shown that they can be degraded rapidly after emission, depending on the atmospheric conditions (Lai et al, 2014;Slade et al, 2014;Arrangio et al, 2015;Bertrand et al, 2018). These studies all demonstrate the importance of oxidation to the aging of organic aerosol and provide motivation for studies of long-range-transported organic aerosol.…”
Section: Introductionmentioning
confidence: 88%
“…Likewise, PMO-1 and PMO-3 exhibit an increase in the number frequency of higher DBE species, which is not observed in PMO-2, supporting the observation of an increased overall aromaticity for these free tropospheric aerosol samples. Many aromatic compounds, such as PAHs are known to be carcinogens, and are a product of incomplete combustion biomass burning and anthropogenic emissions (Perraudin et al, 2006;Bignal et al, 2008).…”
Section: Molecular Formula Aromaticity and Brown Carbonmentioning
confidence: 99%
“…Biomass burning smoke is a significant source of primary and secondary atmospheric particles that have impacts on climate (Bond et al, ), air quality (e.g., Jaffe & Wigder, ; Nie et al, ; Xie et al, ), and health (e.g., Jassen et al, ; Johnston et al, ; Naeher et al, ; Zhang et al, ). Biomass burning emits primary carbonaceous aerosol (both as black carbon and primary organic aerosol; POA; Akagi et al, ; Reid, Koppmann, et al, , and references therein), inorganic aerosol, and vapors, where some vapors may serve as aerosol precursors (e.g., Alvarado & Prinn, ; Bertrand et al, ; Hatch et al, ; Jen et al, ). Biomass burning particle emissions are dominated by an accumulation mode, with a less‐concentrated coarse mode and occasionally a nucleation mode (Reid, Koppmann, et al, ).…”
Section: Introductionmentioning
confidence: 99%